Association between pulmonary function and cardiac enzymes in sickle cell disease - Antwi-Boasiako, Charles (Am J Blood Res, 2021)
Background: There is scarcity of data on association between lung function and cardiac markers in patients with sickle cell disease (SCD). Meanwhile, SCD affects multi-organs in any one population. There seem to be an association between reduced pulmonary function with cardiac dysfunction. The current study examined the association between pulomanry function with cardiac markers in patients with SCD. Methodology: This was a cross-sectional study with cases and controls. The cases (n=117) were made up of patients with SCD. The control subjects (n=58) were voluntary blood donors without SCD. The cellulose acetate electrophoresis was used to determine the genotypes of the study subjects. Blood samples were collected from all the study subjects for full blood count and measurement of cardiac enzymes. The cardiac enzymes measured were lactate dehydrogenase (LDH) and creatine kinase-myocardial band (CK-MB). Lung function test, using the vitalograph was done on all the study subjects. The Global Lung Initiative criteria were used to categorize lung disease as obstruction, restriction, mixed obstruction/restriction and normal. Results: The prevalence of elevated CK-MB and LDH among the SCD patients was 76.92% and 9.40% respectively, higher than the non-SCD controls (51.72% and 0% for elevated CK-MB and LDH respectively). Of all the impaired lung function, lung restriction was prevalent in all the study groups (30.77% and 15.52% for SCD patients and non-SCD controls respectively). In the fully adjusted model, reduced FEV1 was associated with nearly 3.5-fold higher odds of elevated CK-MB (odds ratio 3.35, 95% CI 1.26-8.90, p-value 0.015) in individuals with SCD. Conclusion: Reduced FEV(1) which reflects airflow impairments are associated with CK-MB elevations in patients with SCD, suggesting a possible damage to the cardiomyocytes.